A Survey of Clinical Governance Success in University Hospitals in Tehran - Ali Mohammad Mosadeghrad; Mohammad Arab; Niusha Shahidi Sadeghi (Kerman University of Medical Sciences, 2019)
A Survey of Clinical Governance Success in University Hospitals in Tehran   Mosadeghrad Ali Mohammad1, Arab Mohammad2, Shahidi Sadeghi Niusha3*   1. Associate Professor, Department of Health Management and Economics, Health Information Management Research Centre, School of Public Health, Tehran University of Medical Sciences, Tehran, Iran 2. Professor, Department of Health Management and Economics, School of Public Health, Tehran University of Medical Sciences, Tehran, Iran 3. PhD Student in Health Services Management, Department of Health Services Management, School of Health Management and Information Sciences, Iran University of Medical Sciences, Tehran, Iran *Correspondence: Department of Health Services Management, School of Health Management and Information Sciences, Iran University of Medical Sciences, Valiasr street, Vanak Square, Tehran, Iran Tel: 00982188883334                                               Email: sadeghi.niusha@gmail.com Abstract: Background & Objectives: Clinical Governance (CG) is an organizational strategy for maintaining and improving the quality and safety of patient care and increasing employees' and managers' responsiveness and accountability through developing an appropriate organizational structure and culture as well as developing, implementing and monitoring clinical guidelines, pathways and standards. This study aimed to examine the success of CG implementation in university hospitals, in Tehran, Iran. Methods: In this descriptive analytic study, a researcher-made questionnaire was filled out by managers and CG executive managers of 39 university hospitals in Tehran/ Iran. Data analysis was done through SPSS software and using Pearson, Spearman and logistic regression. Results: Clinical Governance was moderately successful in Tehran university hospitals (58%). The most success was achieved in patient involvement and risk management dimensions and the least success was observed in clinical effectiveness and clinical audit dimensions. Management and leadership and clinical audit had the most effect on CG success. The involvement and commitment of managers and employees in implementing CG were moderate and physicians' involvement and commitment was poor. The length of CG implementation time had significant relationship with managers' and employees' commitment and CG success. Conclusion: Clinical governance was not successful in Tehran university hospitals. Active involvement and commitment of top managers, staff empowering, patient centeredness, evidence-based practice, and clinical audit are necessary for successful CG implementation.   Keywords: Quality management, Clinical governance, Hospital, Critical success factors   Citation: Mosadeghrad AM, Arab M, Shahidi Sadeghi N. A Survey of Clinical Governance Success in University Hospitals in Tehran. Journal of Health Based Research 2019; 5(1): 101-16. [In Persian]